The design and identity of batik tulis product selected of batik manufacturers in Klang Valley / Ahmad Hakim Abdullah - Abdullah, Ahmad Hakim (Universiti Teknologi MARA, Perak, 2020)
Batik Tulis in the Klang Valley has motif and pattern design that identified its own identity. The purpose of this study is to find out the development of the Batik tulis industry in the Klang valley from year 2000 until 2018. Next, it also to study the design and identity of the Batik tulis motif and pattern in the Klang valley from year 2000 until 2018. This study used several methods and approach for data collection consist of interviews, observations and photo documentation. Three Batik tulis manufacturers in Klang Valley have been identified in carrying out this study. The data were then analysed using analytical design approach. The findings showed that, each product of Batik tulis has a uniqueness in terms of subject matters as well as assertions in pattern and designs used. The development of the Batik tulis industry has been changed in terms of design according to the demand of batik users themselves who want differentiation in the design concept of batik products. Most of the batik products in this Klang valley are more focused on the concept of modern and contemporary design. It involves the use of colours, the type of fabrics and the selection of motifs characterized by flora and fauna in modern style. In conclusion, Batik tulis designs and identity in the Klang Valley from year 2000 until 2018 are still retain the originality of the flora and fauna motifs themselves but have made the design of the traditional style to a more modern and contemporary design. However, the design aspect of Hand drawn Batik products in the Klang Valley today needs to be disclosed to the public so that, it can maintain the textile arts, especially the Batik tulis as a Malay textile heritage.